New species, redescriptions and phylogenetic revision of tribe Dacini (Diptera: Tephritidae: Dacinae) from India based on morphological characters - David, K. J.; Ramani, S. (Zootaxa, 2019)
The tribe Dacini comprising four genera, namely Bactrocera Macquart, Dacus Fabricius, Monacrostichus Bezzi and Zeugodacus Hendel, is a derived lineage in Tephritidae. It is one of the most economically important tribes in Tephritidae harbouring several species of quarantine concern across the world. We describe two new species of Bactrocera Macquart, B. (Parazeugodacus) conica David & Ramani, sp. n. & B. (B.) prabhui David, sp. n. from India. Postabdominal structures of males and/or females of 23 species of Bactrocera, 16 species of Zeugodacus and 8 species of Dacus from India are illustrated and described for the first time, which revealed similarities between Dacus and Zeugodacus with respect to epandrial shape and praeputium patterning. Bactrocera is unique in possessing oval shaped epandrium and an unpatterned praeputium. An analysis of phylogenetic relationships between three genera of the tribe Dacini from India based on morphological characters has been attempted for the first time. Cladistic analysis employing 51 characters of 62 species in Dacini, with seven species as outgroups revealed the monophyly of Dacini, Bactrocera and Dacus with supporting nonhomplasious synapomorphies. Ichneumonopsis Hardy, often included in the Gastrozonini, does not possess any synapomorphies of Dacini, eventhough it appeared at the base of the Dacini clade. Zeugodacus was retrieved as a monophyletic sister-group to Dacus based solely on a single homoplasious host plant character, with weak statistcal support.